2018
DOI: 10.1016/j.jpainsymman.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatization and Proneness to Dissociation Among Palliative Care Workers: A Cross-Sectional Study

Abstract: The clinical level of PETD correlates significantly with STS. Further research is needed to understand whether STS is related to the individual's own vulnerability, as reflected by their personal proneness to dissociation, during exposure to death and dying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Workers and volunteers in the hospice care field constantly confront death and the associated grief and trauma which can have deleterious effects on their professional and personal well-being. 26,27 However, working in hospice care also provides opportunities for compassion satisfaction and this contributes to job satisfaction, elevated SWB, and personal growth. In the current pilot study, we investigated the relationship between hope and meaning in life to job satisfaction as assessed by work engagement and SWB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workers and volunteers in the hospice care field constantly confront death and the associated grief and trauma which can have deleterious effects on their professional and personal well-being. 26,27 However, working in hospice care also provides opportunities for compassion satisfaction and this contributes to job satisfaction, elevated SWB, and personal growth. In the current pilot study, we investigated the relationship between hope and meaning in life to job satisfaction as assessed by work engagement and SWB.…”
Section: Discussionmentioning
confidence: 99%
“…Samson and Shvartzman found that there was a negative interaction between increased exposure to death to both work engagement and decreased compassion satisfaction. 26 These authors posited that increased absorption which is characterized by both engrossment and concentration on work leads to higher levels of death exposure with a concomitant increase in both burnout and stress. 26 Our findings raise the question of directionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another characteristic of compassion fatigue is dissociation and derealization (Samson & Shvartzman, 2018). This can be expressed as impairment or lack of consistency in integration of the consciousness, memory, identity, or body image.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the psychology of having to deal with very di cult issues -illness and death -may well have in uenced our participants' responses and their discussion of spirituality issues in the South African context. It is well established that people who deal with human pain and suffering may well experience a degree of what has been termed secondary traumatisation or compassion fatigue [36,37]. The emotional experience of dealing with suffering and death may, of course, also have positive effects and build resilience in carers [38].…”
Section: Discussionmentioning
confidence: 99%